2018
DOI: 10.3390/ma11020253
|View full text |Cite
|
Sign up to set email alerts
|

A Fine Grain, High Mn Steel with Excellent Cryogenic Temperature Properties and Corresponding Constitutive Behaviour

Abstract: A Fe-34.5 wt % Mn-0.04 wt % C ultra-high Mn steel with a fully recrystallised fine-grained structure was produced by cold rolling and subsequent annealing. The steel exhibited excellent cryogenic temperature properties with enhanced work hardening rate, high tensile strength, and high uniform elongation. In order to capture the unique mechanical behaviour, a constitutive model within finite strain plasticity framework based on Hill-type yield function was established with standard Armstrong-Frederick type isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The carbide particles stimulate more nuclei and hinder the growth of grains [26,36]. Consequently, the recrystallization level and grain size of the experimental steel after cold rolling to 95% reduction followed by annealing were much smaller than those of other high-manganese steels without particles annealed at similar temperatures [42,43].…”
Section: Carbides Precipitationmentioning
confidence: 89%
“…The carbide particles stimulate more nuclei and hinder the growth of grains [26,36]. Consequently, the recrystallization level and grain size of the experimental steel after cold rolling to 95% reduction followed by annealing were much smaller than those of other high-manganese steels without particles annealed at similar temperatures [42,43].…”
Section: Carbides Precipitationmentioning
confidence: 89%
“…The presence of Ni in most of these steels has increased the process costs due to the rising unit prices, which is attributed to the global rise in commercial volume and export restrictions [6]. As a result, high-Mn steel has been developed as an alternative material that displays excellent cryogenic properties by adding a large amount of relatively inexpensive Mn [7][8][9]. The LNG fuel tanks of ships are made of a minimum of 10 mm thick high-Mn steels depending on the design requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Koyama et al [10] reported the tensile properties of Fe-17Mn-0.6C steel from RT to -100°C, and the results showed that due to the formation of deformed martensite at -100°C, the strength improved, but at the same time the deformed martensite is a brittle phase, and brittle fracture occurs at -100°C, reducing the plasticity at -100°C. Wang et al [11] studied Fe-34.5Mn-0.04C steel with a grain size of 3.8 μm and found that with decreasing temperature from RT to -150°C, the deformed martensite gradually increased, and the strength gradually increased. The effect of grain size or temperature on the mechanical properties of high manganese steels has been extensively studied; however, only a few studies investigated the effects of grain size and temperature on the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%